L’Affaire Charles Lainé (1818), ou comment la police fabriquait un faux-monnayeur - Étienne Hofmann (Criminocorpus)
Charles Lainé, a locksmith of modest means working at Givenchy-le-Noble in the Pas-de-Calais, was condemned to death in the summer of 1818 for forgery. He had made twelve very crude silver coins which he was preparing destroy when he was arrested. This item of news would have remained unknown if a magistrate had not spontaneously denounced the scandalous behaviour of a police spy who had encouraged Lainé to commit the crime. The magistrate informed the editors of La Minerve française, chief newspaper of the liberal opposition in France. Benjamin Constant, who had only recently been involved in the Wilfrid Regnault case (that of a man condemned to death for a crime he had not committed), published an article and a pamphlet in defence of Lainé, admiting the crime but also accusing the police and those in power of pursuing practices that were as reprehensible as they were pointless, since the locksmith had never before been a forger, did not belong to any criminal group and presented no potential danger to society. Constant’s efforts, combined with those of the lawyer Odilon Barrot and the Director of Criminal Affairs and Pardons Legraverend, led to Lainé’s sentence being commuted to ten years’ imprisonment.